Unusual looking pentatomids: reassessing the taxonomy of Braunus Distant and Lojus McDonald (Hemiptera: Heteroptera: Pentatomidae) - Barão, Kim Ribeiro; Garbelotto, Thereza De Almeida; Campos, Luiz Alexandre; Grazia, Jocelia (Zootaxa, 2016)
The Neotropical genus Braunus Distant is revised. Based on general morphology, Braunus is transferred to the Pentatominae and Lojus is proposed as a junior synonym of Braunus. The male and female genitalia of Braunus sciocorinus (Walker) are described for the first time. Three new species from the Peruvian and Bolivian Andes and from Colombia are described, Braunus machadoi Barão & Garbelotto sp. nov. (Holotype male deposited in AMNH: Peru, Cuzco, 01.XII.2011, C. Weirauch leg.), Braunus gibbus Garbelotto & Barão sp. nov. (Holotype female deposited in AMNH: Bolivia, Santa Cruz, Prov. Caballero, 15–21.X.2001, S. Spector & J. Ledezma leg.), and Braunus prionotus Barão & Garbelotto sp. nov. (Holotype female deposited in MNHN: Colombia, VII.1974, Steinheil leg.), respectively. Also, we describe the internal male and female genitalia of Braunus ocellatus (Thomas) comb. nov. A key to species and comments on subfamilial and tribal placements and on wing polymorphism are provided.